Unmanned aerial vehicle safety assessment modelling through petri Nets - Gonçalves, P. (2017)
Currently we are facing an increasing trend of use of Unmanned Aerial Vehicles (UAV) in various activities both civilian and military. Although there is no legal framework for the operation of these systems, regulatory authorities require the demonstration of a safety level equivalent to manned aircraft. It is known the high vulnerability of the UAV not only to unexpected failures of their systems but also to the environment. The purpose of this paper is to present a safety assessment process modelling of a UAV by Petri Nets, that can be accepted by certifying bodies, considering the recommendations of STANAG 4671 UAV Airworthiness Requirements Specification (USAR) for analysis of fault conditions that lead to the most feared events. It is intended to show through the use of Petri Nets the frequency that the UAV enters the identified states described as most feared events; the ability of the UAV to react after being in a fault situation to the inputs of the operating crew in order to enhance trust and to facilitate the operation authorization process in UAV operations. The results obtained allowed to identify and to define critical areas and corrective actions that will lead to an acceptable level of risk for the regulatory authority.